Nala - Miles, Ellen (Miles, Ellen. Puppy place, 2016)
"Charles and Lizzie Peterson love puppies. Their family fosters these young dogs, giving them love and proper care, until they can find the perfect forever home. Charles can't catch a break. He's never gotten into trouble in class before. Then he spotted that stray dog running around his school. Now it seems like everything he does lands him in the principal's office. Will Charles be able to find that collie pup and give her a forever home?"--Back cover.